The role of intraperitoneal ropivacaine in laparoscopic appendicectomy: a prospective, double‐blinded randomized control Australian study. Issue 1 (24th January 2019) - Huang, Yang Y.; Suthananthan, Arul E.; Hunt, Victoria; Hruby, Jan; Koek, Sharnice; Rowcroft, Alistair; Beh, Han; Jayasundera, Mohan
Abstract : Background: Currently, intraoperative use of local anaesthetic is not routinely given in all laparoscopic appendicectomies. Although its use has been widely studied in laparoscopic hernia repairs, gynaecological laparoscopy and laparoscopic cholecystectomies, there are no published trials of the use of intraperitoneal local anaesthetic during laparoscopic appendicectomy in the Australasian setting. The aim of this study was to determine whether the use of intraperitoneal ropivacaine during laparoscopic appendicectomy will reduce the amount of post‐operative opiate analgesia used, abdominal pain, post‐operative nausea or vomiting, shoulder tip pain and length of hospital stay. Methods: A randomized double‐blinded placebo versus control trial was conducted with patients with clinically diagnosed appendicitis undergoing laparoscopic appendicectomy. Primary outcomes measured were the number of times the patient‐controlled analgesia (PCA) button was pressed post‐operatively and the average and total amount of fentanyl from PCA consumed during the post‐operative period from 0 to 6 h and from 6 to 16 h. Results: A total of 86 patients with 43 patients in the placebo normal saline group and 43 patients in the treatment ropivacaine group were included in the study. During the immediate post‐operative period (0–6 h), there was a statistically significant reduction in the number of times the PCA button was pressed in the ropivacaine group compared to the normal saline group (16 versus 24 times, P  = 0.02). Conclusion: Intraperitoneal ropivacaine has an analgesic effect for patients up to 6 h following emergency laparoscopic appendicectomy. Abstract : Our single Australian centre double blinded randomised control trial demonstrated the use of intraperitoneal ropivacaine has an analgesic effect for patients up to 6 hours following emergency laparoscopic appendicectomy. The study shows a 33% reduction rate in the number of times PCA button was pressed in the intraperitoneal ropivacaine group vs the placebo normal saline group up to 6 hours following surgery.